A Scale Development Study to Determine the Digital Citizenship Levels of Parents - YILMAZ, Onur; İBRET, Bilgin Ünal (Zenodo, 2023)
The purpose of this study is to develop a scale to determine the digital citizenship levels of parents of 7th grade middle school children. In the scale development phase, an item pool containing 79 items was created and narrowed gradually by submitting it to expert opinion. The draft scale was administered to 675 people consisting of parents of 7th grade students in secondary schools affiliated to the Ministry of National Education in Eskişehir province. Principal component analysis and factor analysis were performed to determine the construct validity of the scale, and varimax vertical rotation was applied. According to the results obtained, the digital citizenship scale developed for parents consists of 4 factors and 19 items. These factors explain 60.03% of the total variance explained. This factor structure was also confirmed by confirmatory factor analysis. In order to evaluate the reliability of the scale, Cronbach α (.90) coefficients were calculated for the four factors obtained as a result of varimax rotation and for the whole scale. This .90 Cronbach α value indicates that the scale has a high level of internal consistency. In addition, the data obtained proves that the scale is a valid and reliable scale. The study examined the digital citizenship competencies of the participant group taking into account their personal and demographic variables. As a result, this research demonstrates the development of a valid and reliable scale that can be used to measure the level of digital citizenship.
Keywords: Parents, digital citizenship, scale; 4. Education; 10. No inequality